An assessment of fertilizer quality regulation in Nigeria - Liverpool-Tasie, Lenis Saweda; Auchan, Abba A.; Banful, Afua Branoah (International Food Policy Research Institute, 2010)
Though currently absent, the importance of access to affordable, timely, and good quality fertilizer for increased agricultural productivity and food security in Nigeria is clear. Consequently, this study examines fertilizer quality regulation in Nigeria. Using primary data collected from state officials in charge of fertilizer and from fertilizer production and blending plants, we explore the extent to which the Nigerian fertilizer sector is effectively regulated to ensure the quality of fertilizers delivered to farmers.